Analysis of the implementation of operational risk management in vegetarian culinary business - Adi Wilyanto; Angelina Julia Renaldi; Eni Valentina; Richmond Richmond; Rieza Melinda (Institute of Computer Science (IOCS), 2023)
This study aims to analyze, evaluate and overcome the risk management faced by